Basic proceedings on research and scientific editing. Design of a research project - Ávila Stagg, Dalton; Ávila Gamboa, Dalton (Revista Universidad de Guayaquil, 2010)
Author states basic requirements to set and develop a research project, including financial support. Multicentric groups networks linked by internet and electronic tools reveal as an important effort to get a global and trustable performance on this field.
Keywords: Research project